Design and application of performance evaluation model of school education informatization based on artificial intelligence mode - Zhongyin Zhao; Ng Giap Weng; Sabariah Bte Sharif (ResearchGate, 2024)
Educational informationization is an important part of educational reform. The performance evaluation of educational informationization plays an important role in promoting the development of informationization. Therefore, a performance evaluation model of school education informatization based on artificial intelligence mode is put forward. First, the current situation of school education informatization evaluation is briefly described, summarizing the artificial intelligence technology. The evaluation model of education informatization based on artificial intelligence is established, the performance evaluation index of school education informatization analyzed in detail. The index meets the requirement of input data through quantification and normalization, and the process of performance evaluation is designed. Feasibility and stability of the evaluation method are confirmed by the performance evaluation of school education informatization and the error analysis of the test results.